Ajwain (Trachyspermum ammi Linn): A review on Tremendous Herbal Plant with Various Pharmacological Activity - Shiva; Huzaifa; Singh, Ambika; Mandal, Suraj (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Ajwain is an herbal plant belonging to Apiceae family. Ajwain is also known as Trachyspermum ammi (L). Ajwain is growth in various countries like Pakistan, Iran, Afghanistan and India. Trachyspermum ammi (L) is an annual herb. Ajwain leaves and seed are mainly used by humans and mostly used in cooking for spice. Ajwain is medicinal plant used for various disease. Ajwain act as a germicide and fungicide. Various chemical constituents present in Ajwain like volatile oil, saponins, glycosides, fat, protein, fibre and minerals. Ajwain having the various pharmacological effects and it is various disease. Trachyspermum ammi show antimicrobial, antispasmodic, digestive stimulants, anti-inflammatory and gastroprotective activity. Ajwain relief the menstruation cycle pain. Trachyspermum ammi is used as a medicine. In the future, if we used as a medicine, then in the future we can avoid many diseases, Trachyspermum ammi is an herbal plant, so do not show any side effects. Trachyspermum ammi show various pharmacological activity like Antimicrobial, Antiulcer, Analgesic, Diuretic, Antiviral, Antioxidant, Antihypertensives, Bronchodilator and Antiplatelet.